Phosphorylation of ovine rhodopsin. Identification of the phosphorylated sites. - Thompson, P (1984)
Light-dependent phosphorylation of sheep opsin was obtained in purified discs to which was added a partially purified preparation of rhodopsin kinase. A maximum ratio of 1.8 mol of phosphate/mol of rhodopsin bleached was obtained. Perturbing the lipid bilayer did not alter the phosphorylation ratio. Dephosphorylation in both segments and discs was only achieved when the supernatant fraction from a retina homogenate was added. Complete dephosphorylation required the presence of the detergent dodecyltrimethylammonium bromide in the incubation medium. Treatment of phosphorylated disc membranes with Staphylococcal aureus V8 proteinase generated two membrane-bound fragments, only one of which (V8-S, Mr 12 000) was labelled, together with a soluble seven-residue peptide that contained [32P]phosphoserine. Peptide sequencing, together with subdigestion procedures, localized the phosphorylation sites to serine residues at positions 334, 338 and 343 in the whole sequence and threonine residues at positions 335 and 336.